2021
DOI: 10.1111/dgd.12740
|View full text |Cite
|
Sign up to set email alerts
|

Live visualization of a functional RET‐EGFP chimeric receptor in homozygous knock‐in mice

Abstract: The GDNF Family Ligands (GFLs) regulate neural development and kidney organogenesis by activating the RET receptor tyrosine kinase. Many RET‐dependent developmental processes involve long‐distance cell‐cell communications or cell polarity, which includes cell migration and axon guidance. This suggests that spatiotemporally regulated subcellular localization of RET protein and appropriate propagation of RET signaling in cells are essential for the physiological function of the GFLs. Little is known, however, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The Ret signaling pathway plays a critical role during ENS development. Appropriate levels of Ret activity are crucial for EPC proliferation, migration, and survival [ 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In the ENS, migration, and proliferation are closely connected; decreased proliferation of EPCs leads to decreased EPC migration and vice versa [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ret signaling pathway plays a critical role during ENS development. Appropriate levels of Ret activity are crucial for EPC proliferation, migration, and survival [ 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In the ENS, migration, and proliferation are closely connected; decreased proliferation of EPCs leads to decreased EPC migration and vice versa [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…At early stages of ENS development, enteric progenitor cells (EPCs) migrate to and along the gut [ 1 ]. During this stage, ret is expressed in migrating EPCs and Ret signaling promotes EPC proliferation, migration, and survival [ 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Ret continues to be expressed in neuronal EPCs and neurons into adulthood [ 15 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ret signaling pathway plays a critical role during ENS development. Appropriate levels of Ret activity are crucial for EPC proliferation, migration, and survival [7,[13][14][15][16][17][18][19][20][21]. In the ENS, migration, and proliferation are closely connected; decreased proliferation of EPCs leads to decreased EPC migration and vice versa [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In mice and human, single-cell RNA-sequencing analysis found that Ret is expressed in most ENS neurons in juveniles and adults [22,[38][39][40]. Accordingly, a ret:EGFP transgenic mouse line showed EGFP expression in differentiating neurons [21]. Ret signaling activity is essential for neuronal fate in the ENS.…”
Section: Most Enteric Neurons Are Ret:gfp Positivementioning
confidence: 98%
See 1 more Smart Citation